Published in Zimbabwe - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Zimbabwe`s environmental dilemma by Sam Moyo, Peter Robinson, Yemi Kateree, Stuart Stevenson and Davison Gumbo 165pp 1991 Pbk ISBN 00 7974 09971 ZERO PO Box 5338, Harare ZIMBABWE